Preferensi Konsumen Terhadap Penggunaan Mobil Listrik Teori Technology Acceptance Model dan Theory Of Planned Behavior - Annisa, Syakira Nurul; Hanartyo, Ernawan Dwi (MES Management Journal, 2025)
The negative impacts caused by the use of motor vehicles powered by fossil fuels on the environment have become an increasingly urgent global issue. This study aims to identify the factors that influence the purchase intention of electric vehicles in Indonesia, specifically in the Jakarta area. using the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), along with five additional external factors: price value, perceived risk, environmental awareness, infrastructure availability, and finansial incentive policy. This research uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Region in this study included the people in Jakarta and is surrounding areas who have been exposed to information about electric cars and have basic knowledge about environmentally friendly vehicle technology, totaling 240 respondetns. To obtain the appropriate number of respondents, data collection was carried out through an online questionnaire distributed via Google Forms. The results of the study show that Perceived Usefulness, Attitude, Perceived Risk, Environmental Awareness, and Financial Incentive Policy significantly influence Purchase Intention. However, Perceived Usefulness and Perceived Ease of Use do not affect Attitude; Subjective Norms, Perceived Behavioral Control, and Price Value do not significantly influence Purchase Intention for electric vehicles. Price Value affects Attitude, Environmental Awareness influences both Perceived Usefulness and Subjective Norms, while Infrastructure Availability has no significant effect on Purchase Intention for electric vehicles.